O adolescente e o jovem em conflito com a lei e a escolarização : possibilidade de humanização? - Ferreira, Juliana Zanob (2015)
Several research works on the schooling process of adolescents and young people in conflict with the Law have revealed that they have always been on the margin of the school system, which is thoroughly relevant for the process of knowledge appropriation, psychological development and socialization. Psychologists and educators who deal with these students have always been baffled on what adolescents think of the school and the meaning they have of the school. Current paper analyzes the meaning of the school to adolescents in conflict with the Law and the implications that the schooling process for humanization has within the context of Historical and Cultural Psychology and Historical and Critical Pedagogy. Public policies in social assistance in Brazil are first discussed, due to the fact that the application of social and educational measures to offending adolescents is an integral part of the system. The second section brings forth the manner the school´s attitude in such situations and the pedagogical trends predominant in the school´s day-to-day policy. The third section, dealing with the study of adolescents from Vygotsky´s teaching, investigates how Historical and Cultural Psychology sees the individual´s constitution process, human personality and the development of psychism. In fact, basic concepts for the understanding of the adolescents´ development are developed, among which may be mentioned the concept of crisis, the formation of concepts, the development of higher psychological functions, personal meaning and alienation. Results from interviews with twenty adolescents who had to submit themselves to social and educational measures within a specific program in a town of the northern region of the state of Paraná, Brazil, were analyzed. Data obtained showed that, in the concept of the interviewed adolescents, the school was only a slightly implemented and effective possibility for humanization. Their discourse acknowledged that the school was a place of learning and of historically constructed knowledge but their participation and frequency was null (70% did not attend classes). The school was sometimes characterized as an institution for learning and sometimes as an institution that might take off adolescents and young people from the streets. The meaning of the school oscillated between these two ideas. Results show that, although the school reveals the contradictions of capitalist society where not all have a free access to knowledge and in which (as shown in current research) exclusion is a constant factor, it should make its utmost so that all are introduced to knowledge that contributes towards human development and formation. According to the basic foregrounding of Historical and Cultural Psychology, adolescents develop all their potentialities and form the most complex of scientific concepts during this period in their lives. Consequently, the school should structure itself to invest in these abilities and capacities. Based on the theories above, the elaboration and execution of social assistance policies committed to the schooling process for the humanization of students should be implemented.